2020
DOI: 10.1002/cam4.2815
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: LINC00311 promotes cancer stem‐like properties by targeting miR‐330‐5p/TLR4 pathway in human papillary thyroid cancer

Abstract: Growing evidence has suggested that long noncoding RNAs (lncRNAs) play an essential role in the progression of papillary thyroid cancer (PTC). LncRNA LINC00311 was found to be able to regulate many cellular process in several diseases. However, the function and regulatory mechanism of LINC00311 remains unclear in PTC. In the present study, the results showed that the expression of LINC00311 was upregulated in PTC tissues and cells. Furthermore, knockdown of LINC00311 dramatically suppressed spheroid formation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…In another study, Li et al found that estrogen receptor b (ERb) and lncRNA H19 are overexpressed in PTC-CSC suggesting a positive regulatory interaction of both factors in order to induce and maintain the cancer stem-like features (181). Also, lncRNA LINC00311 seems to have a key role in promoting the stem-like features by regulating the miR-330-5p/TLR4 pathway (182). Moreover, BANCR (BRAF-activated noncoding RNA) regulates the expression of CSC markers LGR5 and EpCAM via the c-Raf/ MEK/ERK signaling pathway (183).…”
Section: Other Noncoding Rnas Deregulated In Ptc-lncrna and Circrnamentioning
confidence: 99%
“…In another study, Li et al found that estrogen receptor b (ERb) and lncRNA H19 are overexpressed in PTC-CSC suggesting a positive regulatory interaction of both factors in order to induce and maintain the cancer stem-like features (181). Also, lncRNA LINC00311 seems to have a key role in promoting the stem-like features by regulating the miR-330-5p/TLR4 pathway (182). Moreover, BANCR (BRAF-activated noncoding RNA) regulates the expression of CSC markers LGR5 and EpCAM via the c-Raf/ MEK/ERK signaling pathway (183).…”
Section: Other Noncoding Rnas Deregulated In Ptc-lncrna and Circrnamentioning
confidence: 99%
“…miR-193a-5p directly targets SPOCK1 in hepatocellular carcinoma to repress its malignancy ( 39 ). Additionally, miR-330-5p and miR-326 have both been demonstrated to play tumor-suppressive roles in PTC progression ( 20 , 21 ). However, research on miR-193a-5p in PTC is limited.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-206 suppresses drug resistance to Euthyrox by targeting MAP4K3 ( 19 ). A recent study showed that miR-330-5p mediates the positive regulation of long intergenic non-protein-coding RNA 003311 on cancer stem-like features in PTC ( 20 ). miR-326 suppresses PTC cell proliferation and metastasis by inhibiting MAPK1 and erb-b2 receptor tyrosine kinase (ERBB) 4 ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several miRNAs and lncRNAs have found to be dysregulated in multiple subtypes of TC. Recently, two lncRNAs, lncRNA -LINC00311 and lncRNA-H19 were identified as specific promotors of cancer stem-like properties in PTC ( Li et al, 2018 ; Gao et al, 2020 ). Similarly, two miRNAs: miR-148a and antisense-miR-21, were both found to significantly inhibit TCSCs in ATC cells ( Haghpanah et al, 2016 ; Sheng et al, 2016 ).…”
Section: Autophagy and Epithelial-to-mesenchymal Transition: Invasion...mentioning
confidence: 99%